The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1063/1.1833580
|View full text |Cite
|
Sign up to set email alerts
|

In situ surface-enhanced Raman spectroscopy of monodisperse silver nanowire arrays

Abstract: Highly ordered two-dimensional arrays of monodisperse coinage metal nanowires embedded in an alumina matrix have been prepared. When light is propagating in the direction of the long axis of the nanowire, plasmon-enhanced absorption and light guidance of the nanowire were observed by optical microspectroscopy and scanning near-field optical spectroscopy and compared to Mie scattering theory. By selectively dissolving the matrix at a constant etching rate, we detected in situ and ex situ the surface-enhanced Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…This can be explained by the fact that the gold helices are not physically connected with each other and that the spacing between them is larger than their evanescent field if the light is incident in the direction of their long axes. Similar results were observed by other groups measuring the transmission through silver or gold nanowire arrays in AAO matrices [38]. The refractive index of gold was derived from the analytical model of Etchegoin et al [39] and matches experimental data reported by Johnson and Christy [40].…”
supporting
confidence: 63%
“…This can be explained by the fact that the gold helices are not physically connected with each other and that the spacing between them is larger than their evanescent field if the light is incident in the direction of their long axes. Similar results were observed by other groups measuring the transmission through silver or gold nanowire arrays in AAO matrices [38]. The refractive index of gold was derived from the analytical model of Etchegoin et al [39] and matches experimental data reported by Johnson and Christy [40].…”
supporting
confidence: 63%
“…As a thumb of rule, the distribution in the length of electrodeposited nanowires in porous template channels increases with the wire length. Therefore, in order to have uniform length MNWs for SERS studies either the deposition time must be shortened, yielding nanodots rather than nanowires [Kartopu et al, 2006;Wang et al, 2006], or the initially long MNWs must be levelled by an appropriate post treatment, such as mechanical polishing [Kartopu et al, 2008b] and ion milling [Sauer et al, 2005]. In the latter case, a chemical etching may be applied to increase the exposed area of nanowires ( Fig.…”
Section: Substrates For Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…An in situ chemical etching (in dilute H 3 PO 4 ) is used to probe the temporal change in the SERS spectrum of analyte molecules adsorbed on MNWs/Ag nanowires (Fig. 15c) [Sauer et al, 2005]. The signal intensity first increases to a maximum and then decreases rapidly before it completely vanishes.…”
Section: Substrates For Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…8 Other deposition techniques support the growth of nanostructures using grated substrates or embedded matrices. 9 Still other techniques confine material to 1-D tubular structures [10][11] or arrange granular material in a linear fashion. [12][13] The VLS process, one of the methods frequently applied to grow 1-D ZnO nanostructures, was first described in 1965 for the Au-assisted growth of Si whiskers, 14 and is currently a well-understood system.…”
Section: Introductionmentioning
confidence: 99%